DNA sequencing using ISFET-based technology - Teh, Jian Sen (2015)
ISFET is an emerging technology that has the potential to revolutionize pH sensing and other ion-based sensing applications. Firstly, this thesis proposes a digital-based ISFET system for DNA sequencing application that minimizes the use of analogue front end and directly converts pH into a 10-bits binary output using of digital comparators and counters. To facilitate high sensing resolution and sampling rate, it uses a clock frequency of 200MHz and is able to reach a maximum sampling rate of 775kHz The proposed design was simulated in standard 65nm/1.2V CMOS technology, offering a resolution of 0.0437 pH and consuming only 28.4 pJ per conversion. Secondly, this thesis proposes a characterization plan for ISFETs. A simple circuit was used to minimize parasitic effects from other components. A total of 468 n/p-typed ISFETs will be characterized, where effects of type of threshold voltage, base length, W/L ratio and top metal size will be studied. A layout of a single cell was implemented in standard 60nm/1.2V CMOS technology.